Towards a Feminist Cinematic Ethics Claire Denis, Emmanuel Levinas and Jean-Luc Nancy - Hole, Kristin (Edinburgh University Press, 2015)
Towards a Feminist Cinematic Ethics develops an account of non-normative ethics that can be used to think about filmmaking and viewing, using two philosophers-Emmanuel Levinas and Jean-Luc Nancy, and the work of filmmaker Claire Denis. In an accessible and engaging manner, it offers new readings of Denis' films, situating them within larger feminist, postcolonial and queer debates about identity and difference. Using a generative methodology, the book works towards a mutually challenging and productive relationship between cinematic ideas and philosophical concepts.